Creating the need in Mexico: the IAEA's technical assistance programs for less developed countries (1958-68). (1st October 2020) - Mateos, Gisela; Suárez-Díaz, Edna
ABSTRACT: Nuclear technologies and skills were not easily sold as tools for development for the less developed countries. Beginning in 1958, the International Atomic Energy Agency, as part of the United Nations Expanded Program of Technical Assistance, looked to create the need for nuclear technical assistance around the world, with the expectation that countries would climb a supposed developmental ladder that went from radioisotope applications in medicine, agriculture and industry among others, and up to the construction of nuclear power reactors. The case of Mexico reveals the heterogenous levels of professionalization of the different nuclear disciplines existing in the country, and the lack of meaningful connections between technical assistance requests and the developmental model favored by the Mexican government during the 1960s. We oppose the historicity of nuclear physics, radiochemistry, and nuclear engineering in this country, to the telos of development.